Network of sacrificial territories: the links between dumps and sanitary landfills in Costa Rica - Mora-Solano, Sindy (2025)
Introduction: this paper examines the network of sacrifice zones created by the areas where solid waste from the Greater Metropolitan Area (GAM) of Costa Rica has been deposited. Objective: based on the concepts of network territories by Rogério Haesbaert and sacrifice zones by Steve Lerner, the study examines the connections between the Río Azul garbage dump and the La Carpio and El Huazo landfills. Methodology: the paper employs a comparative case study approach. Administrative and journalistic sources are used to characterize the network of sacrifice zones. Conclusions: the article concludes that, despite the differences between modalities in waste management practices, whether open dumps or sanitary landfills, the territories forming this network are characterized by environmental degradation, institutional demands, and social conflicts.